Analisa Strategi Digitalisasi UMKM Food And Beverage Selama Pandemi Covid-19 di kota Batam - eryc, eryc (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
This research study aims to gain in-depth knowledge and understanding of the selected factors that will affect the survival of the food and beverage industry at the MSME level, namely small and medium enterprises, especially small and medium restaurants located in Batam city. This research will be carried out using quantitative research methods which will use IBM SPSS to carry out the test analysis. Reliability and validity testing will be carried out using Cronbach's Alpha and Keyser Meyer Olkins (KMO). Correlation and multiple linear regression will be used to prove the hypothesis. The factor indicators studied, namely the significant impact of digitalization, product innovation, and funding correlated with the sustainability of MSMEs, especially in the F & B sector in the city of Batam in proving that the three factor indicators have a positive relationship and influence the continuity of the F & B MSME business in the city. Batam. The results of this study have proven that digitization, product innovation, and funding have a positive relationship to the survival of F&B MSMEs, meaning that MSMEs can begin to consider and possibly implement digitalization into the system to improve business performance. Unique product innovation should also be considered as one of the most important factors to attract customers and create value for MSMEs.